Determination of Thiafentanil in Plasma Using LC–MS. (9th December 2019) - Cox, Sherry; Bergman, Joan; Allender, Matthew C; Beckmen, Kimberlee; Lance, William
Abstract: A new method of analysis has been developed and validated for the determination of thiafentanil in plasma. After protein precipitation, samples were separated on an XBridge BEH C18 column and quantified using mass spectrometry. The mobile phase was a mixture of water with 0.1% formic acid and acetonitrile with 0.1% formic acid (90:10). The standard curve ranged from 0.1 to 25 ng/mL. Intra- and Inter-assay variability for thiafentanil was less than 10%, and the average recovery was greater than 95%. The lower limit of quantification was 0.1 ng/mL. This is the first validated method for thiafentanil analysis in plasma.